Social dilemma and vitamin D deficiency: a cross-sectional study of nutritional rickets in children ages 6 months to 24 months - S., Sajid; Khan, Irfan; K., Khalid; A., Khalil; Marwat, Zahid I.; N., Shah (International Journal of Contemporary Pediatrics, 2019)
Background: In developing countries, malnutrition’s is one of the challenges that still need to be addressed. Undernutrition is usually a result of the unavailability of food and/or repeated infections in children. Countries with comparatively lower per-capita incomes as well as those with middle per-capita income have its increased prevalence in younger age. Social dilemma of mothers, like exclusively breastfeeding, heavy clothing’s and practice of keeping babies inside the doors, lead vitamin D deficiency and ultimately into nutritional rickets. The objective of this study was to determine the frequency of factors leading to nutritional rickets in children ages 6 months to 24 months. Methods: This cross-sectional study was conducted at Department of Pediatrics, Ayub Teaching Hospital, Abbottabad, Pakistan from March to December 2017. After inclusion/exclusion criteria, total 160 patients of rickets were observed. Detailed history followed by vitamin D level (<15 ng/ml) was measure. Data was analyzed by SPSS-22 and all documents were locked with principal author. Results: Present study showed that 62% children were in age ranged 6-12 months and 38% children were in age range 13-24 months. Mean age was 12 months with SD±2.16. Seventy nine percent children were male, and 21% children were females. More over 52% children had exclusive breast feeding, and 48% children did not have exclusive breast feeding. Similarly, 15% children had limited sun-light exposure and 85% children did not have limited sun-light exposure. Conclusions: Present study concluded that a lack of health education and sunlight exposure and exclusive breastfeeding were the significant risk factors contributed to nutritional rickets among children of Abbottabad, Pakistan.